Design and construction of a subsonic open-circuit wind tunnel - Garro-Fernández, Fiorella (2024)
The Wind Energy Research Laboratory of the Instituto Tecnológico de Costa Rica (LIENE) has designed and built an open circuit subsonic wind tunnel operating by suction, with a 30x30 cm test section, where the aerodynamic behavior of models in a controlled air flow can be characterized. The tunnel is powered by a 1 horsepower motor and can operate at wind speeds between 7 and 15 m/s; the instrumentation installed allows the measurement of lift forces up to 100 N and drag forces up to 50 N. The following work describes the procedure for the conception, fabrication, instrumentation, and characterization of the tunnel, from its theoretical basis to its design and operation.